Penerapan Sanksi Adat Bagi Pelaku Persetubuhan terhadap Anak Kandung di Desa Tulikup Gianyar - Ni Made Ayu Trimayukti; I Nyoman Gede Sugiartha; I Ketut Sukadana (Fakultas Hukum, Universitas Warmadewa, 2020)
Sexual intercourse with children is a very cruel crime especially the perpetrators of the crime of sexual intercourse against the child is the biological father of the victim. The Criminal Law Code has regulated the act of sexual intercourse namely Article 284-288. The specific crime of sexual intercourse with children has also been regulated in Law No. 35 of 2014 concerning Child Protection. The people of Bali believe in the existence of a scale and noetic which, if something goes wrong, is believed to disturb the magical balance. In customary law, sexual intercourse with biological children is included in the Gamia Gemana offense and has been regulated in Awig-awig Desa Adat Tulikup Kelod. Based on these problems, this study was made with the aim of uncovering the factors that caused the crime of sexual intercourse against biological daughter in the village of Tulikup Gianyar and how the application of traditional sanctions for perpetrator of intercourse against a biological daughter in the village of Tulikup Gianyar. This research employed empirical research methods by analyzing quantitative data. The results of the study stated that the sexual needs that were not fulfilled by the wife, the low awareness of the perpetrator in the application of religious teachings, and the condition of the house which was always quiet were the causes of intercourse against a biological daughter in the village of Tulikup Gianyar. In addition to being subjected to positive sanctions in the form of imprisonment and fines, the perpetrator of sexual intercourse against biological children in Tulikup Village was also subject to sanctions that have been regulated in Awig-awig Kelik Tulikup Adat Village namely in the form of Sangaskara Danda (sanctions in the form of ceremonies) which must be carried out by the perpetrator and also the victim.